Song-Based Reading Module and Learning through Playing Approach for Children with Learning Disabilities - Sabin, Hanifah; Pang, Vincent; Bullare@Bahari, Muhammad Idris (Journal of ICSAR, 2019)
Reading skills are essential skills since early childhood education. For children with disabilities in learning (CWDL), specific reading-learning methods should be provided with regard to the problems faced by the children. Hence, this concept paper provides an alternative in teaching and learning using the Modul Riang Ria Membaca (MRRM) based on songs and learning approach through playing. This study used a literary research method to obtain data for the development of reading modules for children with learning disabilities. The findings of the study were the “Riang Ria Reading Module” and the suggestion of the implementation of a fun and meaningful early reading instruction for CWDL. The use of songs as well as the integration of hands-on activities in the form of physical games creates an atmosphere of teaching and learning that can attract attention and focus of students with learning disabilities.